Vitamin and mineral status of trained competitive cyclists during one year of training - Schirmer, G. P.; Keith, R. E.; Gropper, S. S.; Pascoe, D. D.; Weese, J. (Medicine & Science in Sports & Exercise, 1996)
It was found that highly trained cyclists (N = 15) following self-selected diets without supplementation were able to maintain plasma vitamin/mineral levels within normal limits. They were also able to consume greater than RDA for almost all nutrients. Implication. A self-selected diet of good content is sufficient to maintain appropriate vitamin and mineral levels in hard-training athletes.